2007
DOI: 10.1063/1.2722731
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic origins of surface states on nitride surfaces

Abstract: We report a systematic and comprehensive computational study of the electronic structure of GaN and InN surfaces in various orientations, including the polar c plane as well as the nonpolar a and m planes. Surface band structures and density-of-states plots show the energetic position of surface states, and by correlating the electronic structure with atomistic information we are able to identify the microscopic origins of each of these states. Fermi-level pinning positions are identified, depending on surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
210
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(237 citation statements)
references
References 45 publications
25
210
2
Order By: Relevance
“…Thus, one is faced with the classical situation of a non-polar III-V semiconductor surface, where the bulk band gap is free of intrinsic surface states. This agrees well with theoretical calculations of the band structure of the InN(1010) surface [39], where the filled and empty surface states are located energetically within the valence and conduction band, respectively.…”
Section: B Electronic Propertiessupporting
confidence: 79%
“…Thus, one is faced with the classical situation of a non-polar III-V semiconductor surface, where the bulk band gap is free of intrinsic surface states. This agrees well with theoretical calculations of the band structure of the InN(1010) surface [39], where the filled and empty surface states are located energetically within the valence and conduction band, respectively.…”
Section: B Electronic Propertiessupporting
confidence: 79%
“…The main significant difference is that no surface states are within the fundamental band gap [58,62,63]. The filled states are energetically located at the valence band maximum, whereas the empty states are well above the conduction band minimum ( Fig.…”
Section: Wurtzite Innmentioning
confidence: 99%
“…In contrast, both calculated empty states have stronger, but different, dispersions. The overall minimum is again at the Γ-point within the fundamental band gap [58,62]. No experimental data of the surface states of GaN(1120) is reported, yet.…”
Section: Wurtzite Ganmentioning
confidence: 99%
“…[16][17][18] To date, however, the practical device applications of InN-based materials have been severely limited by the presence of extremely large residual electron density and the uncontrolled surface charge properties, as well as the difficulty in achieving p-type conductivity. 8,[19][20][21][22][23][24][25][26][27][28][29][30] For example, in general, the currently reported nominally undoped InN is n-type degenerate, with the residual electron densities in the range of ∼ 1 × 10 18 cm −3 , or higher. 8,11,25,[31][32][33][34] Moreover, it has been generally observed that there exists a very high electron concentration (∼ 1 × 10 13−14 cm −2 ) at both the polar and nonpolar grown surfaces of InN films, 19,35 and the Fermi-level (E F ) is pinned deep into the conduction band at the surfaces; 19,20,29,30 similar electron accumulation profile has also been measured at the lateral nonpolar grown surfaces of [0001]-oriented wurtzite InN nanowires.…”
mentioning
confidence: 99%